The Role of Village Government in the Orderly Land Administration in Dayeuhluhur Village, Tempuran District, Karawang Regency as an Implementation of Agrarian Reform - Guntara, Deny; Wahyudi, Rikes; Gunawan, Endang Ano; Rahman, M. Rafly Dwi; Dewi, Cindy Aulia; Putri, Shilva Alya; Putra, Daffa Fauzan Hanif Angkoso (Journal of Comprehensive Science, 2024)
Order of village land is the process of managing and regulating land at the village government level. According to Law Number 6 Year 2014, villages are authorized to manage local governance matters, including those related to land issues. This research aims to understand the implementation of land administration systems in Dayeuhluhur Village, Tempuran Subdistrict, Karawang Regency, West Java Province. The method used is juridical-empirical, incorporating interviews and direct observations in Dayeuhluhur Village, along with data analysis from literature as supporting evidence. Data collected is qualitatively analyzed to explain findings derived from observations and journal records. Data was gathered from primary sources such as interviews and observations, as well as secondary sources like documents. The study's findings indicate that the land administration system in Dayeuhluhur Village functions effectively. However, it also reveals that the role of the Dayeuhluhur Village government in land administration is not yet ideal due to several reasons, including weaknesses in human resources, lack of coordination with relevant agencies, deficiencies in village land administration systems and procedures, and inadequate community awareness of the importance of orderly land administration. Therefore, due to these inhibiting factors, the village government is less effective in ensuring orderly land administration, both internally and externally. By addressing these barriers, it is hoped that the village government's role in ensuring orderly land administration can be maximized to benefit the community and the village as a whole.